Positron emission tomography–CT prediction of occult nodal metastasis in recurrent laryngeal cancer. Issue 5 (25th February 2017) - Rosko, Andrew; Birkeland, Andrew; Shuman, Andrew; Prince, Mark; Bradford, Carol; Wolf, Gregory; Worden, Francis; Eisbruch, Avraham; Srinivasan, Ashok; Wong, Ka Kit; Spector, Matthew E.
ABSTRACT: Background: The purpose of this study was to evaluate the predictive value of positron emission tomography (PET)‐CT in identifying occult nodal metastasis in clinically and radiographically N0 patients with recurrent laryngeal cancer undergoing salvage laryngectomy. Methods: Retrospective review of 46 clinically and radiographically N0 patients with recurrent laryngeal cancer who underwent a PET‐CT examination before salvage laryngectomy with neck dissection from January 1, 2002, to December 31, 2014, was performed. Results: Two patients (16.7%) had true‐positive PET‐CT results, whereas 10 patients (83.3%) had false‐negative scans, 1 patient (2.9%) had a false‐positive result and 33 patients (97.1%) had a true‐negative PET‐CT. The sensitivity of PET‐CT was 16.7% (95% confidence interval [CI], 3.5% to 46.0%) with a specificity of 97.1% (95% CI, 83.8% to 99.9%), positive predictive value (PPV) of 66.7% (95% CI, 20.2% to 94.4%), and negative predictive value (NPV) of 76.7% (95% CI, 62.1% to 87.0%). Conclusion: PET‐CT has poor sensitivity and NPV making PET‐CT an imperfect predictor of nodal disease in recurrent laryngeal cancer. © 2017 Wiley Periodicals, Inc. Head Neck 39: 980–987, 2017